The Role of the Effects of Endoplasmic Reticulum Stress on NLRP3 Inflammasome in Diabetes - Lv, Shuangyu; Li, Xiaotian; Wang, Honggang (Frontiers in Cell and Developmental Biology, 2021)
Endoplasmic reticulum is an important organelle for protein synthesis, modification, folding, assembly and transportation of new peptide chains. When the folding ability of endoplasmic reticulum proteins is impaired, the accumulation of unfolded or misfolded proteins leads to endoplasmic reticulum stress. The nucleotide-binding oligomerization domain-like receptor family, pyrin domain-containing 3 (NLRP3) inflammasome can induce the maturation and secretion of Interleukin-1beta (IL-1β) and IL-18 through activating caspase-1. It is associated with many diseases.Studies have shown that ERS is closely related to NLRP3 inflammasome in many diseases including diabetes. However, the mechanism of the effects of ERS on NLRP3 inflammasome in diabetes has not been fully understood. This review summerize the recent research about the effects of ERS on NLRP3 inflammasome and its mechanism in diabetes to provide ideas for the relevant basic research in the future.